Bone measurements interact with phenotypic measures in canine Duchenne muscular dystrophy - Schneider, Sarah M.; Mackey, Macie L.; Wilkinson, Savannah; Guo, Lee-Jae; Nghiem, Peter P. (Frontiers in Veterinary Science, 2025)
Duchenne muscular dystrophy (DMD) is an X-linked muscle disease with weakness, loss of ambulation, and premature death. DMD patients have reduced bone health, including decreased femur length (FL), density, and fractures. The mdx mouse model has paradoxically greater FL, density, and strength, positively correlating with muscle mass. Bone morphology has not been extensively studied in the genetic homolog, golden retriever muscular dystrophy (GRMD). The aim of this study was to compare bone and muscle characteristics in GRMD dogs to understand their relationship to muscle function and density. We hypothesized that GRMD bone measurements would be altered similarly to DMD and would correlate with muscle strength and density. Eighteen variably aged and mixed gender dogs (6 each dystrophic, carrier, normal) were studied by computed tomography (CT) and bone measures were compared with various muscle functional measurements. FL, density, and volume and muscle density of several pelvic limb muscles were assessed. Dystrophic dogs showed some boney and muscle density changes on CT analysis compared to carriers and normal dogs. In GRMD, bone measurements were highly correlated with several other functional outcome measures, including eccentric contraction decrement, hip joint angle, and muscle volume/density. This novel experiment demonstrates an impact of dystrophy on bone outcome measures and provides observations on their correlation with functional outcomes.